The Influence of Supervisory Practices and the Leadership Style of the Ma'had Director on the Discipline of Ma'had Students - Robi Alhamda; Supriadi Supriadi (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examined the influence of supervisory practices and the leadership style of the Ma'had Director on the discipline of students at Ma'had Al-Jami'ah, State Islamic University (UIN) Sjech M. Djamil Djambek Bukittinggi. As a residential Islamic educational institution, Ma'had Al-Jami'ah plays a vital role in fostering students' character, spirituality, and discipline. A quantitative survey design was employed, involving mahasantri residing at the Ma'had during the odd semester of the 2025–2026 academic year. Data were collected through validated and reliable structured questionnaires and analyzed using multiple linear regression to examine both partial and simultaneous effects. The results revealed that supervisory practices had a positive and significant influence on student discipline (r = 0.631, p = 0.002), while the leadership style of the Ma'had Director also significantly enhanced disciplinary behavior (r = 0.680, p 0.001). Simultaneously, both variables explained 69.6% of the variance in student discipline (R = 0.834, R² = 0.696, p 0.001). These findings highlight the importance of integrating effective supervision with humanistic and spiritually oriented leadership to strengthen discipline within higher education residential institutions.